Global terrorism - Bhatt, Ashok (New Delhi Saurabh Publishing House, 2007)
This book of Terrorism examines the underlying causes of terrorism and details concrete measures for addressing them. The study of these roots and risk factors of terrorism needs to be an essential component of any counter-terrorist strategy. The Roots of Terrorism not only examines what makes terrorists tick, but also what can be done to prevent their emergence. The terrorist activities have explored the conscious and sub-conscious motivations of terrorists, few have spelled out policymakers in liberal democracies can do address these concerns. These chapters, thus, represent not only the state of the art in the study of the causes of terrorism, but are uniquely practical in their approach.
Keywords: Terrorism